To question of influence of flowage on durability of details - Дудников, Анатолий Андреевич; Беловод, Александра Ивановна; Решитько, Руслан Петрович; Шевченко, Владимир Владимирович (Eastern-European Journal of Enterprise Technologies, 2011)
The questions of influence of flowage are considered at ordinary and oscillation treatment on the size of work-hardening